Adiponectin Modified BMSCs Alleviate Heart Fibrosis via Inhibition TGF-beta1/Smad in Diabetic Rats - Meng, Ke; Cai, Huabo; Cai, Simin; Hong, Yucai; Zhang, Xiaoming (Frontiers in Cell and Developmental Biology, 2021)
Background: Accumulating evidence suggested that bone marrow mesenchymal stem cells (BMSCs) have therapeutic potential for diabetes and heart diseases. However, the effects of BMSC on reducing myocardial fibrosis need to be optimized. This study aimed to investigate the mechanism of adiponectin (APN) modified BMSCs on myocardial fibrosis in diabetic model in vivo and in vitro. Methods: The high-fat diet (HFD) combined with streptozotocin (STZ) injection were used to induced DCM rat model and H9c2 cells were cultured under a high glucose medium. The BMSCs were modified by APN plasmid or APN siRNA, then transplanted to the diabetic rats by a single tail-vein injection, or co-cultured with H9c2 cells. Results: We demonstrated that diabetic rats showed typical DCM symptoms, such as decreased cardiac function, accumulation of pathological lesions and collagen expression. However, these impairments were significantly prevented by the APN modified BMSCs treatment while no effects on APN siRNA modified BMSCs treated diabetic rats. Moreover, we confirmed that APN modified BMSCs could attenuate the expression of TGF-beta1/smad to suppress the myocardial fibrosis in the diabetic rats and high glucose induced H9c2 cells. Conclusions: The present results for the first time showed that APN modified BMSCs exerted protection on cardiac fibrosis via inhibiting TGF-beta1/smad signal pathway in diabetic rats. Our findings suggested that APN modified BMSCs might be a novel and optimal therapy for the DCM in future.